THE COMPARISON ON NEGOTIATION STYLES PREFERENCE BETWEEN THAI AND BHUTANESE - Promsri, Chaiyaset (International Journal For Research In Business, Management And Accounting, 2019)
The purpose of this research is to compare negotiation styles preference between Thai and Bhutanese in order to examine whether there is significant difference in negotiation between people from these two countries. A total of nineteen students both Thais and Bhutaneses who enrolled in the Business Negotiation and Presentation course at a selected public university were participated in this study. Data were collected through a 28-item of negotiation styles questionnaire, which encompassed five dimensions of negotiation styles including collaborating, accommodating, competing, compromising, and avoiding styles. Findings indicated that the most dominant negotiation style of Thais and Bhutaneses was collaborating style while the least preferred negotiation style of people from both countries was avoiding style. Results of interdependent samples t-test analysis revealed no significant differences of preferred negotiation styles in nationality.